1999
DOI: 10.1136/hrt.82.5.594
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and long term outcome in cases with fetal diagnosis of congenital heart disease: Italian multicentre study

Abstract: Objectives-To analyse the evolution and outcome in utero and after birth of infants with a fetal diagnosis of congenital heart disease. Design-Inclusion criteria were the fetal diagnosis of congenital heart disease, confirmed postnatally or postmortem, and a complete follow up in utero and after birth. Setting-20 centres operating prenatal echocardiographic screening. Patients-847 cases were included in the study. Gestational age at diagnosis ranged from 15-39 weeks; in 370 cases (43.7%) the diagnosis was made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
56
3
5

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 24 publications
10
56
3
5
Order By: Relevance
“…4,[8][9][10][11][12] Our report evaluated the risk for hospital mortality in infants born with major CHDs who were supported with intensive care. In all, 25 (26%) of the infants died before undergoing surgical procedures, similar to that reported in Fesslova et al 3 …”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…4,[8][9][10][11][12] Our report evaluated the risk for hospital mortality in infants born with major CHDs who were supported with intensive care. In all, 25 (26%) of the infants died before undergoing surgical procedures, similar to that reported in Fesslova et al 3 …”
Section: Discussionsupporting
confidence: 77%
“…3,4 We included the presence of extracardiac anomalies in the logistic regression model, and this was not identified as an independent risk factor. We also found a higher frequency of associated non-cardiac anomalies than Patel et al 4 Other investigators reported on outcome of fetuses diagnosed with CHDs (29% were terminated), 3 or of infants diagnosed with CHDs within the first year of life. 1,13 Our inclusion of infants with CHDs who were resuscitated at birth is more relevant to clinical practice in the NICU.…”
Section: (33%)mentioning
confidence: 99%
See 1 more Smart Citation
“…Abzugrenzen ist der isolierte Septum-primum-Defekt von einem erweiterten Sinus coronarius, der meist infolge einer in ihn mündenden links persistierenden oberen Hohlvene auftritt [23]. Atrioventrikuläre Septum-Defekte (AVSD) sind mit 16 -18 % die am häufigsten pränatal diagnostizierten Herzfehler [20,21]. Sie umfassen einen Septum-primum-Defekt, einen hochliegenden Ventrikelseptum-Defekt sowie eine gemeinsame AV-Klappe.…”
Section: Cme Fortbildung/continuing Education 143unclassified
“…Anomalien der Trikuspidalklappe machen 6 -12 % der pränatal diagnostizierten Vitien aus [20,21]. Die Trikuspidaldysplasie und die Ebstein'sche Anomalie zeichnen sich durch einen dysplastischen und insuffizienten Trikuspidalklappenapparat aus, wobei die Segel verdickt erscheinen.…”
Section: Atrioventrikularklappenunclassified